Fodor's 2009 San Francisco. - Fodor's Travel Guides (Firm) (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to San Francisco, with maps and information on hotels and restaurants, shopping and entertainment, Alcatraz Island, cable cars, and other interesting sites.
"Pullout map inside"--Cover.
Cover title: San Francisco 2009.
Map on inside cover.
Includes bibliographical references and index.
Young Adult
Keywords: San Francisco (Calif.) -- Guidebooks; San Francisco (Calif.) -- Guidebooks